2017
DOI: 10.1016/j.asr.2017.06.038
|View full text |Cite|
|
Sign up to set email alerts
|

Extra-terrestrial construction processes – Advancements, opportunities and challenges

Abstract: The Open University's repository of research publications and other research outputs Extra-terrestrial construction processesadvancements, opportunities and challenges

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…These tests proved to be successful and a 3D printer has been permanently installed at the ISS for both emergency part creation and for general component production at the ISS for on-going experiments. In addition to studying small FFF 3D printing, significant research has been conducted in the area of using in-situ materials to create large construction projects off-earth [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…These tests proved to be successful and a 3D printer has been permanently installed at the ISS for both emergency part creation and for general component production at the ISS for on-going experiments. In addition to studying small FFF 3D printing, significant research has been conducted in the area of using in-situ materials to create large construction projects off-earth [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Sieving of the feedstock materials is conventionally regarded as a profound and processrelated necessity for powder bed fusion processes but material sieving on the lunar surface is expected to pose as a considerable challenge for bulk material handling, due to the presence of electrostatic charges in the lunar regolith 42 (further addressed in Section 3.7) thus obstructing the free flow of the feedstock regolith onto the powder bed. Potential mitigation of such an environment/material-related setback could be an integrated sieving system with charge dissipation capabilities.…”
Section: Layer Thicknessmentioning
confidence: 99%
“…As previously highlighted by Lim et al, the significant lack of atmosphere on the lunar surface is also expected to have a strong contribution into heat dissipation mechanisms. As opposed to terrestrial conditions in which heat is propagated via the conduction and convection principles, radiations is expected to be the predominant head dissipation mechanism which is known to be less effective 42 .…”
Section: Atmospherementioning
confidence: 99%
“…Missions to mars will require a temporary base on the Moon, consequently several options to create structures on the Moon using available lunar soil are discussed and under investigation. [1][2][3][4][5][6][7][8][9][10][11] If insitu materials could be used on the Moon (such as regolith or regolith derived concrete), to build large civil engineering structures, then extensive amounts of mass launched from Earth could be avoided, making space exploration more economical and hence possible. 12 For a mind-setting, this communication starts with a closer look to the environmental conditions present on the Moon and their effect on envisaged fabrication technology for structural constructive elements.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other difficulties like handling of liquid binders under vacuum circumstances or potential freezing of materials in a wetmix based printing process can be avoided. 11 A basic calculation showed that for sintering based technologies e.g. instead of a laser on the Moon the sun can be used.…”
Section: Introductionmentioning
confidence: 99%